HUBUNGAN KEKUATAN CORE STABILITY DENGAN VO2 MAX PADA LANSIA PANTI WERDHA BUDI MULIA 3 JAKARTA - Hikmah Asri Ramadhani (2022)
Background : Elderly is a process of decreasing physiological functions of the body that will cause health problems known as degenerative diseases, the body will experience a decline so that at the aging stage it will maintain normal body structure and function so that the aging process affects changes in humans, namely physical changes. In this study, core stability measuring instruments were used in the form of sit ups and vo2 max using the three minute walking test. The purpose of this study was to determine whether there is a relationship between core strength and stability with vo2 max in the elderly at the Budi Mulia 3 Nursing Home in Jakarta. The research method used cross sectional research design using correlative descriptive. The number of samples used in this study were the elderly who were in Panti Werdha Budi Mulia 3 Jakarta, aged over 60 years with a total of 31 people. The results of this study were measured using SPSS data. The conclusion in this study is that there is no significant relationship between core strength stability and vo2 max in the elderly.